Buying Beauty: Female Beauty Consumption in the Modern British World - Clark, Jessica P. (History compass, 2016)
In recent years, historians of American, French, and global beauty consumption have charted the rich relationship linking beautifying goods to self-fashioning and the body, historical subjectivities, and the construction of gender and racial identities. Yet, despite productive attention to male beauty in Britain and its relationship to masculinity and the history of sexuality, little attention has been devoted to women's beauty consumption in modern British history. This article surveys literature on U.S., French, and global female beauty consumption to argue for further study of beauty commodities and their production by historians of modern Britain and its empire. The history of British women's beauty consumption intersects with important historical developments that make it worthy of exploration, most notably the use of beautifying and grooming goods as tools for self-fashioning in the British imperial context. Ultimately, a focus on female beauty consumers and producers positions women as key figures in the formation of or resistance to the British imperial project.